Multi-objective bat algorithm tuned optimal FOPID controller for robust aircraft pitch control. (2017) - Kumar, Parvesh; Narayan, Shiv
Algorithms based on swarm intelligence, to resolve robustness issue for the optimisation problem of the real world applications, like pitch control of an aircraft system, is nowadays common amongst researchers. Bat algorithm is one of the voiced algorithms in today's context. This paper is an explanatory attempt to discuss tuning of fractional order PID and classical PID parameters using bat algorithm for the weighted multi-objective optimisation. The optimised values obtained from the techniques have been implemented for the pitch control of an aircraft system to obtain the desired robust response. In this paper, a mixed sensitivity H∞ problem has been designed and simulated using MATLAB programming. The efficacy of the results has been established compared with other tuning methods. It has been shown that the design of multi-objective bat algorithm tuned fractional order controller gives better results.